Pengaruh Variasi Temperatur Artificial Aging 150ᵒC, 170ᵒC dan 190ᵒC Terhadap Sifat Kekerasan dan Struktur Mikro Al-2024 - Okta Rianda; Zulhanif Zulhanif; Harnowo Supriadi (JURNAL MECHANICAL, 2022)
The use of aluminum in the automotive industry has increased since 1980 and continues to increase in line with the increase in the number of motorized vehicles in Indonesia. Automotive components derived from aluminum alloys are required to have good strength. To have good strength, aluminum is usually combined with elements such as: Cu, Si, Mg, Zn, Mn, Ni, and so on. Aluminum-Copper Alloy (Al-Cu) is widely used in automotive components such as engine components that work at high temperatures, for example in the piston and cylinder head of the combustion motor. The mechanical properties of Al-Cu are needed and fulfilled in automotive components, therefore it is necessary to increase the mechanical properties of the Aluminum-Copper (Al-Cu) alloy. This research will be carried out using aluminum alloy Al-Cu with 2024 series which will receive heat treatment at a temperature of 4500C with quenching cooling method and then receive artificial aging treatment with temperature variations of 1500C, 1700C and 1900C. This research was conducted to determine the comparison of hardness and microstructure of aluminum before and before receiving artificial aging treatment. In this study, the results of the chemical composition test were obtained with the percentage of Al of 90.6% and the percentage of Cu being 5, 90%. The highest hardness value is found in Al-Cu material with artificial aging process with a temperature variation of 1900 C, the hardness value is 74.4 (HRB) which has an increase of 24% from the hardness value of the material without heat treatment. The results of the microstructure test showed that the Al-Cu material after the artificial aging process at a temperature of 1900C had more black grains and the Al-Cu grain boundaries tended to be more dense and regular. This can be interpreted that in materials that are treated with artificial aging there are precipitates or the formation of a second phase which causes the material to be harder and have better mechanical properties.Keywords: Alluminium Alloy, Artificial Aging, Hardness, Micro Structure